2013
DOI: 10.4102/ajlm.v2i1.76
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Tuberculosis co-infection impacts T-cell activation markers but not the numbers subset of regulatory T-cells in HIV-1 infected patients

Abstract: BackgroundTuberculosis (TB) has been shown to accelerate the clinical course of HIV infection, but the mechanisms by which this occurs are not well understood. Regulatory T-cells (Tregs) are known to dampen hyperactivation of the immune cells, but it remains unclear whether hyperactivation of T-cells in HIV infection is associated with a decrease of Tregs and what the effect Mycobacterium tuberculosis (MTB) co-infection has on T-cell activation and Tregs.ObjectivesIn this study, we aim to evaluate whether acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
3
4
2
Order By: Relevance
“…Immune activation has been used as predictor of HIV disease progression [25], which has previously been shown with CD38 expression on CD8 + T cells [26]. Persistent infections reportedly impact HIV disease progression triggering excessive T-cell activation [15,27,28]. Here, we showed that increased expression of CD38 on T cells of HIV/TB co-infected compared to HIV-infected individuals, which is in line with others [27,29] as previously proposed due to peripheral immune activation [29].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Immune activation has been used as predictor of HIV disease progression [25], which has previously been shown with CD38 expression on CD8 + T cells [26]. Persistent infections reportedly impact HIV disease progression triggering excessive T-cell activation [15,27,28]. Here, we showed that increased expression of CD38 on T cells of HIV/TB co-infected compared to HIV-infected individuals, which is in line with others [27,29] as previously proposed due to peripheral immune activation [29].…”
Section: Discussionsupporting
confidence: 92%
“…Persistent infections reportedly impact HIV disease progression triggering excessive T-cell activation [15,27,28]. Here, we showed that increased expression of CD38 on T cells of HIV/TB co-infected compared to HIV-infected individuals, which is in line with others [27,29] as previously proposed due to peripheral immune activation [29]. TB had also reported to foster immune activation by increasing the expression of CD38 on T-cell subsets [30,31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Numerous literatures have established that immune activation is a direct measure of HIV disease progression [45,[59][60][61] , which has previously been shown with CD38 expression on CD8 + T cells [43,46,62] . Multiple studies have also shown that concomitant with HCV, HBV, and MTB can directly impact HIV disease progression with excessive T-cell activation in the peripheral blood [40,[63][64][65] . Increased expression of CD38 on both CD4 + and CD8 + T-cells of HIV-TB co-infected subjects has been described relative to HIV mono-infection [63,66,67] .…”
Section: Co-infectionmentioning
confidence: 99%
“…Multiple studies have also shown that concomitant with HCV, HBV, and MTB can directly impact HIV disease progression with excessive T-cell activation in the peripheral blood [40,[63][64][65] . Increased expression of CD38 on both CD4 + and CD8 + T-cells of HIV-TB co-infected subjects has been described relative to HIV mono-infection [63,66,67] . This was also consistent with existing evidences that explain the association of HIV/TB co-infection with sustained levels of peripheral activation in immune compartment following pathogenic persistence [67][68][69] .…”
Section: Co-infectionmentioning
confidence: 99%